Smarten up! : how to increase your brain power - Yepsen, Roger B. (Boston : Little, Brown, 1990)
Tips for getting maximum power from your brain with food, exercise, and other external forces. Provides test and experiments to determine how each of our individual minds works.
Includes bibliographical references and index.
6 13 18 19 25 26 38
Keywords: Brain -- Juvenile literature; Intellect -- Juvenile literature